2022
DOI: 10.3889/oamjms.2022.10348
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Secretome-Hypoxia Mesenchymal Stem Cells on Regulating SOD and MMP-1 mRNA Expressions in Skin Hyperpigmentation Rats

Abstract: BACKGROUND: Ultraviolet B (UVB) radiation is the main factor causing hyperpigmentation. MSC secretome contains bioactive soluble molecules such as cytokines and growth factors that can accelerate skin regeneration. However, the molecular role of the secretome in hyperpigmentation is still unclear. AIM: This study aimed to determine the effect of secretome hypoxia mesenchymal stem cells (S-HMSC) gel on the expression of superoxide dismutase (SOD) and matrix metalloproteinases (MMP-1) genes in skin tissue of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…23,25 UVB radiation has been shown to increase oxidative stress due to DNA damage so that it can activate melanin formation pathways such as the nuclear factor kappa beta (NF-kB) pathway and the melanocyte inducing transcription factor (MITF) pathway. 19,26 In the process of melanogenesis, tyrosinase plays a role in converting L-tyrosine into L-3,4-dihydroxyphenylalanine (L-DOPA). 27 L-DOPA is then oxidized to L-DOPAquinone, which then forms eumelanin and pheomelanin 28 Thus causing a blackish color on the skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,25 UVB radiation has been shown to increase oxidative stress due to DNA damage so that it can activate melanin formation pathways such as the nuclear factor kappa beta (NF-kB) pathway and the melanocyte inducing transcription factor (MITF) pathway. 19,26 In the process of melanogenesis, tyrosinase plays a role in converting L-tyrosine into L-3,4-dihydroxyphenylalanine (L-DOPA). 27 L-DOPA is then oxidized to L-DOPAquinone, which then forms eumelanin and pheomelanin 28 Thus causing a blackish color on the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary metabolite compounds derived from petai fruit peel extract such as flavonoids, phenolics, saponins, tannins and terpenoids are thought to inhibit MITF activity through inhibition of the PI3K/Akt pathway. 4,19,20 Previous research has also reported that flavonoid compounds can inhibit TGF-β via the cAMP/protein kinase A pathway and induce GLI2, then suppress MITF, a central transcription factor in melanogenesis. 30 Inhibitory MITF will prevent the synthesis of tyrosinase enzyme, so Ltyrosine cannot be converted into L-DOPA.…”
Section: Discussionmentioning
confidence: 99%